Coaching as a strategy to improve the teaching and learning process of english for students attending the eighth level of the onsite program at the army polytechnic school-department of language during the March -August semester, 2010 - Missura, Cecilia (2012)
This work was done with the purpose to search a way to help students finish the English levels at Army Polytechnic School with a high knowledge of the language in its four abilities within high standards. It is also meant to help them know the necessity of learning a language and its importance throughout their lives and careers, the more they know, higher would be the possibility of obtaining a better job. In this project ¿COACHING¿ is the method presented that would help teachers and students increase their performance applying the different tools a coach has on hand to help people. The research took place at the Army Polytechnic School, Department of Languages, through a survey done to 5 classes of the eighth levels with a total of 102 students and 4 teachers. Within the analysis of the survey we found that the working hypothesis is accepted and that coaching would help the teachers and students in their learning process, and the null hypothesis is rejected...